2008
DOI: 10.1039/b802808g
|View full text |Cite
|
Sign up to set email alerts
|

Dendronised block copolymers as potential vectors for gene transfection

Abstract: A series of block copolymers containing a dendronised cationic block for efficient DNA binding and a poly(ethylene glycol) block for encapsulation of the complex were synthesised in a modular fashion using a combination of click chemistry and ring-opening metathesis polymerisation. DNA binding experiments, investigated using gel electrophoresis, dynamic light scattering and transmission electron microscopy, showed that all polymers prepared in this study strongly complex DNA and self-assemble into polyion comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 28 publications
0
9
0
1
Order By: Relevance
“…Agarose Gel Electrophoresis. 38 170 ng of pDNA and 10 μL of 12.5, 25, and 50 μM gemini surfactants 12-16 solution was loaded with 5 μL glycerol into 1% agarose gel containing 2 μL of ethidium bromide (0.5 mg/mL). Electrophoresis was carried out at 100 V in Tris buffer for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Agarose Gel Electrophoresis. 38 170 ng of pDNA and 10 μL of 12.5, 25, and 50 μM gemini surfactants 12-16 solution was loaded with 5 μL glycerol into 1% agarose gel containing 2 μL of ethidium bromide (0.5 mg/mL). Electrophoresis was carried out at 100 V in Tris buffer for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…This study focuses on a new flexible approach for the synthesis of drug delivery submicroparticles functionalized by several molecules (therapeutic agent, fluorescent dye, etc) using a standardized procedure and nonaggressive methodology based on click chemistry and Ring‐Opening Metathesis Polymerization (ROMP). Recently, several authors6–12 have shown that ROMP polymers can be functionalized by “click‐chemistry” either by functionalizing the monomer or after polymerization of a precursor monomer bearing an alkyl bromide. Nevertheless, to the best of our knowledge, combination of ROMP and “click‐chemistry” has never been reported in dispersed media.…”
Section: Introductionmentioning
confidence: 99%
“…The norbornene benzylic bromide precursor ( 4 , Scheme ) was prepared by monosubstitution of α,α′-dibromo- p -xylene ( 1 , Scheme ) with the sodium anion of (±)- exo -5-norbornene-2-methanol . The exo -adduct was used as the steric hindrance around the carbon–carbon double bond is less than in the case of the endo -compound, enabling an easier approach of reactants during the postpolymerization modification (e.g., thiyl radicals in thiol–ene chemistry).…”
Section: Resultsmentioning
confidence: 99%
“…Compound 4 (Scheme ) was prepared by a reported procedure, starting from distilled (±)- exo -5-norbornene-2-methanol . The synthesis was repeated on 5 g scale and compound 4 was isolated after column chromatography with 53% yield.…”
Section: Methodsmentioning
confidence: 99%